Perovskite thin film preparation method and solar cell
Through the combination technology of nanoimprinted film and ultra-thin additive layer, the incomplete reaction problem caused by the density of lead iodide thin film in the two-step deposition method is solved, and the photoelectric performance and film quality of perovskite solar cells are improved.
Patent Information
- Application Number
- CN202411819129.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When preparing perovskite solar cells, the lead iodide film is too dense, resulting in incomplete chemical reaction of organic amine salts and increased residues, which reduces the film quality and photoelectric properties.
Nanoimprinted film assisted in the preparation of ordered lead iodide films, and an ultra-thin additive layer was deposited on its surface, and spin-coating and annealing were used to form a high-quality perovskite absorption layer.
It effectively reduces the residue of lead iodide, improves the quality of the perovskite absorption layer and the photoelectric conversion efficiency, reduces the defect density, and improves the performance of perovskite solar cells.
Smart Images

Figure CN119300680A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and more specifically, relates to a method for preparing a perovskite film with the assistance of a nanoimprint film, and a single-junction perovskite solar cell prepared by the method. Background Art
[0002] Perovskite solar cells are regarded as a revolutionary next-generation solar cell technology due to their high power conversion efficiency (PCE), easy manufacturing and low cost. Since the advent of perovskite solar cells, the PCE of the most advanced devices has increased by more than 26% in the past decade, making it one of the most commercially promising candidate products thanks to its advanced architecture and technology. The quality of the perovskite active layer is a key factor in the photovoltaic performance of perovskite solar cells, so the preparation of high-quality perovskite films has always been a research focus. Currently, the commonly used methods for preparing perovskite films in the laboratory include spin coating, anti-solvent assisted method, two-step deposition method and blade coating. These methods have their own characteristics, aiming to improve the quality and consistency of the film, thereby optimizing the performance of the battery.
[0003] Spin coating is one of the most commonly used laboratory methods. It forms a uniform film by dropping a perovskite precursor solution onto a substrate and rotating the substrate. Spin coating is simple and easy to operate, and the thickness and uniformity of the film can be precisely controlled, but it is not suitable for large-scale production. The antisolvent-assisted method is to quickly add a volatile antisolvent to the film surface during or after spin coating to promote the rapid nucleation and crystallization of the film, thereby obtaining a high-quality film. The antisolvent-assisted method often relies on toxic solvents. The two-step deposition method is a process in which a dense lead iodide (PbI2) film is first deposited, and then a polycrystalline perovskite film is formed by reacting with an organic amine salt (such as methylamine iodide, CH3NH3I). By preparing separately in two steps, the uniformity and crystallinity of the film can be better controlled, thereby improving the quality of the film, which is very advantageous for the preparation of large-area perovskite solar cells.
[0004] However, the current two-step deposition method research still has certain limitations. The photoelectric performance of the prepared perovskite film is low, and it is easy to be too dense when preparing the lead iodide film. This causes incomplete chemical reaction with organic amine salts, and too much unreacted PbI2, organic ammonium salts and other residues remain. These residues are easy to become defect centers, thereby reducing the quality of the film. Therefore, it is very important to prepare a lead iodide film with good order, consistent density and appropriate roughness.
[0005] In CN115605063A, a uniform single-layer PS microsphere template film is obtained by depositing a PS microsphere dispersion solution on the substrate surface, and then a lead iodide solution is prepared on the surface of the PS microsphere template film, and then the PS microsphere template is washed with an organic solution of toluene to obtain a uniform and orderly porous lead iodide film after etching, which significantly reduces the residual lead iodide. The resulting perovskite solar cell has an area of 1.01cm2 under a standard sunlight, and the device conversion efficiency of the ordered porous lead iodide preparation reaches 19.17%. The preparation steps of this method are relatively cumbersome, the quality requirements of the dispersion solution are high, and the size of the gap between the holes cannot be controlled. Summary of the invention
[0006] The purpose of the embodiments of the present application is to provide a method for preparing a perovskite film and a solar cell. When preparing a lead iodide film in a two-step deposition method, a nanoimprint film and an additive are combined to prepare an ordered lead iodide film with suitable density, so that when preparing a perovskite absorption layer, the organic amine salt can more easily penetrate into the lead iodide film and react with it more completely, thereby reducing the content of unreacted lead iodide, effectively improving the diffusion rate of the two-step preparation method, reducing the defect density, and improving the quality of the perovskite absorption layer film and the photoelectric conversion efficiency of the device.
[0007] To achieve the above objectives, the technical solutions adopted in this application are as follows:
[0008] A method for preparing a perovskite film comprises the following steps: providing a battery substrate, preparing a lead iodide film on the battery substrate; using a nanoimprint film to further improve the lead iodide film to form a patterned lead iodide film, and pressing the lead iodide film into an ordered shape; depositing an ultra-thin additive layer on the surface of the patterned lead iodide film by a vacuum deposition method; applying a prepared organic ammonium salt solution on the surface of the additive layer to form an ammonium salt film, and obtaining a perovskite absorption layer after spin coating and annealing.
[0009] Furthermore, the surface of the nanoimprint film is provided with a plurality of array-distributed strip-shaped protrusion structures, and the strip-shaped protrusion structures can be selected from arched, cone-shaped, square-shaped and other structures; or, the surface of the nanoimprint film is provided with a plurality of array-distributed point-shaped protrusion structures, and the point-shaped protrusion structures can be selected from cone-shaped, cylinder-shaped, cube-shaped and other structures.
[0010] In one embodiment, the nanoimprint film material is flexible polysiloxane (PDMS).
[0011] In this embodiment, the cross-sectional width of the strip-shaped protrusion structure or the width of the dot-shaped protrusion structure is defined as d1, and the spacing between the strip-shaped protrusion structures or the spacing between the dot-shaped protrusion structures is d2. Optionally, d1 can be selected from 0.5 to 2 μm according to actual conditions, preferably 1 μm, and d2 is 0.5 to 3 μm, preferably 2 μm.
[0012] Furthermore, the battery substrate includes a conductive substrate and a hole transport layer thereon; or, the battery substrate is a back electrode, a silicon bottom battery, a tunneling layer and a hole transport layer stacked in sequence, and the silicon bottom battery is a non-velvet structure.
[0013] The lead iodide film is deposited on the battery substrate by vacuum evaporation. The vacuum range of the lead iodide film during evaporation is 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~8Å / S, the heating crucible temperature is 380℃~500℃, and the evaporation time is 30min~4h.
[0014] The vacuum degree of the additive layer during vacuum deposition is in the range of 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~1Å / S, the heating crucible temperature is 100℃~200℃, the evaporation time is 5min~20min, and the thickness is 0.5~5nm.
[0015] The additive layer is an organic amine halide, including propylenediamine bromide (PDADBr), propylenediamine iodide (PDADI), butylamine iodide (BAI), dodecanediaminium bromide (DDDADBr), and the like.
[0016] The additive layer may also be bromide, chloride and rubidium, including cesium bromide (CsBr), cesium fluoride (CsF), cesium chloride (CsCl), rubidium chloride (RbCl), rubidium bromide (RbBr) and the like.
[0017] The organic ammonium salt solution is prepared by dissolving formamidine iodide (FAI), formamidine bromide (FABr) and methylammonium chloride (MACl) in an organic solvent in a certain proportion, wherein the volume ratio of FAI and FABr is between 10:1 and 1:10; the volume ratio of MACl to the two ammonium salt additives FAI and FABr is between 0% and 50%, and the solution concentration is controlled between 0.5-2 M; the organic solvent includes at least one of ethanol, isopropanol, methanol, dimethylformamide (DMF), G-butyrolactone (GBL), dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMA), and the solvent volume ratio is between 0-3:10-7.
[0018] More specifically, the amount of the organic ammonium salt solution solvent is 50-200ul, the rotation speed of the spin coating is 1000-5000rpm, the rotation time is 10-80s, the annealing humidity is 10-50%, the annealing temperature is 60-180°C, and the annealing time is 10-50min.
[0019] The present invention also provides a perovskite solar cell prepared by the above method, the structure of which comprises, from bottom to top, a conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer, and an electrode layer.
[0020] Specifically, the conductive substrate is one of fluorine-doped tin oxide (FTO) and indium tin oxide (ITO).
[0021] The hole transport layer is nickel oxide (NiO x ), molybdenum disulfide (MoS2), molybdenum oxide (MoO x ) is composed of at least one of the following.
[0022] The perovskite absorption layer is an ABX3 structure, where A is an organic cation, including CH3NH3 + (MA + ), NH2CH=NH2 + (FA + ), cesium ion (Cs + ), rubidium ions (Rb + ), potassium ion (K + ) or sodium ion (Na + )
[0023] B is a metal cation, including lead ions (Pb 2+ ), tin ions (Sn 2+ ), cadmium ions (Cd 2+ ), calcium ion (Ca 2+ )
[0024] C is a halogen anion, including F - , Cl - Br - ,I - At least one of .
[0025] The electron transport layer is zinc oxide (ZnO), tin dioxide (SnO2), titanium dioxide (TiO2), [6,6]-phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C 60 ) at least one of.
[0026] The electrode layer is at least one of gold (Au), silver (Ag), and copper (Cu).
[0027] An embodiment of the present application also provides a method for preparing a perovskite solar cell, comprising the steps of: providing a conductive substrate, preparing a hole transport layer on the surface of the conductive substrate, preparing a perovskite absorption layer on the surface of the hole transport layer, preparing an electron transport layer on the surface of the perovskite absorption layer, and preparing an electrode layer on the surface of the electron transport layer, wherein the perovskite absorption layer is obtained by the above-mentioned perovskite thin film preparation method.
[0028] The method for preparing a perovskite solar cell provided in the embodiment of the present application has at least the following beneficial effects:
[0029] The preparation method of the present invention utilizes the advantages of easy preparation, low price and high repeatability of the nanoimprint film. After depositing the traditional lead iodide film, the lead iodide film is subjected to orderly pattern processing, so that the subsequent organic ammonium salt can more easily penetrate into the lead iodide film, the reaction is more complete, and the residual lead iodide content can be effectively reduced, thereby improving the film quality of the perovskite absorption layer and improving the photoelectric conversion efficiency of the device.
[0030] The nanoimprint film used in the preparation method of the present invention has good flexibility and is not likely to cause damage to the traditional lead iodide film, thereby reducing the film quality of the perovskite absorption layer.
[0031] The preparation method of the present invention deposits an ultra-thin additive layer on the prepared lead iodide film, so that the additive can effectively passivate the perovskite absorption layer. Compared with doping the additive in the organic ammonium salt, there is no need to consider whether the additive can be dissolved in the solvent, and the permeability is better, which can effectively improve the film quality of the perovskite absorption layer and improve the device performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or exemplary technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a process flow chart of preparing a perovskite film in an embodiment of the present invention;
[0034] Figure 2 A schematic diagram of the structure of a single-junction perovskite solar cell provided in an embodiment of the present invention;
[0035] Figure 3 A diagram showing the steps for preparing a perovskite film in an embodiment of the present invention;
[0036] Figure 4-Figure 6 Schematic diagram of an optional structure of the nanoimprint film M1 in an embodiment of the present invention;
[0037] Figure 7 FIG. 4 is a schematic diagram of the structure of the nanoimprint film M1 in an embodiment of the present invention.
[0038] 10. Battery substrate; 11. Lead iodide film; 12. Patterned lead iodide film; 13. Additive layer; 14. Ammonium salt film; M1. Nanoimprint film; 20. Conductive substrate; 21. Hole transport layer; 22. Perovskite absorption layer; 23. Electron transport layer; 24. Electrode layer. DETAILED DESCRIPTION
[0039] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0040] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0041] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, "multiple" means two or more, unless otherwise clearly and specifically defined. "Several" means one or more, unless otherwise clearly and specifically defined.
[0042] In the description of the present application, it should be understood that the terms "center", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0043] Reference throughout the specification to "one embodiment" or "an embodiment" means that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment of the present application. Thus, when the phrases "in one embodiment" or "in some embodiments" appear in various places throughout the specification, not all references are to the same embodiment. Furthermore, in one or more embodiments, the particular features, structures, or characteristics may be combined in any suitable manner.
[0044] See also Figure 1 The present invention provides a method for preparing a perovskite film assisted by a nanoimprint film, comprising the steps of: providing a battery substrate 10, preparing a dense lead iodide film 11 of a certain thickness on the battery substrate 10; using a nanoimprint film M1 to further improve the lead iodide film 11 to form a patterned lead iodide film 12, and pressing the lead iodide film into an ordered shape; depositing an ultra-thin additive layer 13 on the surface of the patterned lead iodide film 12 by a vacuum deposition method; forming an ammonium salt film 14 on the surface of the additive layer 13 with a prepared organic ammonium salt solution and spin coating, and obtaining a perovskite absorption layer 22 after annealing. The nanoimprint film M1 used in the present application is a flexible material that will not cause damage to the film layer. The nanoimprint film M1 is provided with an orderly arranged pattern structure on the surface. After lamination, the lead iodide film 11 can form a patterned structure, which effectively increases the diffusion and penetration of ammonium salt molecules to improve the crystallization efficiency and film quality of the perovskite.
[0045] The cell substrate 10 can select a suitable substrate according to the actual application. When applied to a single-junction solar cell, the cell substrate 10 can be a conductive substrate 20 and a hole transport layer thereon; or, when applied to a stacked solar cell, the cell substrate 10 can be a back electrode, a silicon bottom cell, a tunneling layer and a hole transport layer stacked in sequence, and the silicon bottom cell is a non-velvet structure.
[0046] The lead iodide film 11 is deposited on the battery substrate 10 by vacuum evaporation. More specifically, the vacuum range of the lead iodide film 11 during evaporation is 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~8Å / S, the heating crucible temperature is 380℃~500℃, and the evaporation time is 30min~4h.
[0047] The patterned lead iodide film 12 can increase the surface area of the lead iodide film, thereby increasing the reaction contact area between the organic ammonium salt solution and the lead iodide film.
[0048] At the same time, an ultra-thin additive layer 13 is formed on the surface of the patterned lead iodide film 12 by vacuum deposition. On the one hand, it can passivate the lead iodide residues in the reaction process. On the other hand, the additive is first deposited on the surface of the lead iodide film, which can improve the crystallization quality of the perovskite film.
[0049] The additive layer 13 is deposited in vacuum at a vacuum degree of 5×10 -4 Pa~1×10 -2Pa, the evaporation rate range is 0.1Å / S~1Å / S, the heating crucible temperature is 100℃~200℃, the evaporation time is 5min~20min, and the thickness is 0.5~5nm.
[0050] The additive layer is an organic amine halide, including propylenediamine bromide (PDADBr), propylenediamine iodide (PDADI), butylamine iodide (BAI), dodecanediaminium bromide (DDDADBr), and the like.
[0051] The additive layer may also be bromide, chloride and rubidium, including cesium bromide (CsBr), cesium fluoride (CsF), cesium chloride (CsCl), rubidium chloride (RbCl), rubidium bromide (RbBr) and the like.
[0052] The organic ammonium salt solution is prepared by dissolving formamidine iodide (FAI), formamidine bromide (FABr) and methylammonium chloride (MACl) in an organic solvent in a certain proportion, wherein the volume ratio of FAI and FABr is between 10:1 and 1:10; the volume ratio of MACl to the two ammonium salt additives FAI and FABr is between 0% and 50%, and the solution concentration is controlled between 0.5-2 M; the organic solvent includes at least one of ethanol, isopropanol, methanol, dimethylformamide (DMF), G-butyrolactone (GBL), dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMA), and the solvent volume ratio is between 0-3:10-7.
[0053] More specifically, the organic ammonium salt solution has a solvent volume of 50-200ul, a rotation speed of 1000-5000rpm, a rotation time of 10-80s, an annealing humidity of 10-50%, an annealing temperature of 60-180°C, and an annealing time of 10-50 min.
[0054] For further information, see Figure 4~Figure 7 In order to ensure that the patterned thin film structure obtained during imprinting is more regular and has a larger surface area, the surface of the nanoimprint film M1 is provided with a plurality of array-distributed strip-shaped protrusion structures, and the strip-shaped protrusion structures can be selected from arch, cone, square and other structures; or, the surface of the nanoimprint film M1 is provided with a plurality of array-distributed point-shaped protrusion structures, and the point-shaped protrusion structures can be selected from cone, cylinder, cube and other structures. In this embodiment, the cross-sectional width of the strip-shaped protrusion structure or the width of the point-shaped protrusion structure is defined as d1, and the spacing between the strip-shaped protrusion structures or the spacing between the point-shaped protrusion structures is defined as d2. Optionally, d1 can be selected from 0.5 to 2 μm according to actual conditions, preferably 1 μm, and d2 is 0.5 to 3 μm, preferably 2 μm.
[0055] In one embodiment, specifically, the nanoimprint film material is flexible polysiloxane (PDMS).
[0056] The imprint template was soaked and cleaned with ethanol, dried on a hot stage, and the cured PDMS solution was cast on the imprint template. It was checked that there were no bubbles in the solution, and then it was placed in a vacuum oven for degassing and curing. Finally, the imprint template was taken out and the prepared PDMS nanoimprint film M1 was peeled off for standby use. The soaking and cleaning time was 30~300s, the hot stage temperature was 70~150℃, the vacuum oven temperature was 50~150℃, and the oven time was 30min~4h.
[0057] See also Figure 2 The embodiment of the present invention also provides a single-junction perovskite solar cell, comprising a conductive substrate 20, a hole transport layer 21, a perovskite absorption layer 22, an electron transport layer 23, and an electrode layer 24, wherein the perovskite absorption layer 22 is prepared by the above method. The preparation steps of the perovskite solar cell are as follows: providing a conductive substrate 20, preparing a hole transport layer 21 on the surface of the conductive substrate 20, preparing a perovskite absorption layer 22 on the surface of the hole transport layer 21, preparing an electron transport layer 23 on the surface of the perovskite absorption layer 22, and preparing an electrode layer 24 on the surface of the electron transport layer 23.
[0058] The specific preparation steps of the perovskite solar cell are as follows:
[0059] S11: Providing a conductive substrate 20 and cleaning, respectively, using ethanol, methanol, acetone cleaning 15 min, drying 30min;
[0060] Optionally, the conductive substrate 20 is one of fluorine-doped tin oxide (FTO) and indium tin oxide (ITO).
[0061] S12: preparing a hole transport layer 21 on the surface of the conductive substrate 20;
[0062] Optionally, the hole transport layer 21 is nickel oxide (NiO x ), molybdenum disulfide (MoS2), molybdenum oxide (MoO x ) is composed of at least one of;
[0063] Optionally, the hole transport layer 21 is formed by spin coating, and the hole transport layer dispersion is evenly coated on the surface of the conductive substrate 20, the spin coating speed is 1000-5000 rpm, and the spin coating time is 10-100 s; after the spin coating is completed, an annealing operation is performed, the annealing temperature is 300-600° C., and the annealing time is 10-50 min;
[0064] Optionally, the hole transport layer 21 is formed by magnetron sputtering, the conductive substrate 20 is sequentially placed on a magnetron sputtering substrate, dust on the surface is blown off with an ear-cleaning bulb, the magnetron sputtering substrate is placed in a magnetron sputtering chamber, the program is started, and it is taken out after the program is finished;
[0065] S13: preparing a perovskite absorption layer 22 on the hole transport layer 21, wherein the perovskite absorption layer 22 is prepared by a two-step method and has a thickness of 0 to 1500 nm;
[0066] Specifically, see Figure 1 , using a vacuum deposition method, the lead iodide material is placed in a crucible, the battery substrate 10 prepared in the above steps is placed in a vacuum deposition substrate, vacuuming is performed, the crucible is heated until the required evaporation rate is reached, the baffle is opened for evaporation, and a dense lead iodide film 11 with a thickness of 300-1000 nm is prepared; then the lead iodide film 11 is further improved by pressing using a nanoimprint film M1 prepared in advance, and annealing treatment is performed on an annealing table, and the nanoimprint film M1 is removed after annealing to form a patterned lead iodide film 12; the additive material is placed in a crucible, the imprinted battery substrate is placed in a vacuum deposition substrate, vacuuming is performed, the crucible is heated until the required evaporation rate is reached, the baffle is opened for evaporation, and an additive layer 13 is obtained on the patterned lead iodide film 12; finally, the prepared organic ammonium salt solution is evenly coated on the surface of the above additive layer 13, and then annealing treatment is performed within a certain humidity range to obtain a perovskite absorption layer 22.
[0067] More specifically, the vacuum range of the lead iodide film 11 during evaporation is 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~8Å / S, the heating crucible temperature is 380℃~500℃, and the evaporation time is 30min~4h.
[0068] More specifically, when the nanoimprint film M1 is used on the lead iodide film 11 , the annealing temperature is 50-100° C., and the annealing time is 10-100 seconds.
[0069] More specifically, the vacuum range of the ultra-thin additive layer 13 during evaporation is 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~1Å / S, the heating crucible temperature is 100℃~200℃, the evaporation time is 5min~20min, and the thickness is 0.5~5nm.
[0070] The organic ammonium salt solution is prepared by dissolving formamidine iodide (FAI), formamidine bromide (FABr) and methylammonium chloride (MACl) in an organic solvent in a certain proportion, wherein the volume ratio of FAI and FABr is between 10:1 and 1:10; the volume ratio of MACl to the two ammonium salt additives FAI and FABr is between 0% and 50%, and the solution concentration is controlled between 0.5-2 M; the organic solvent includes at least one of ethanol, isopropanol, methanol, dimethylformamide (DMF), G-butyrolactone (GBL), dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMA), and the solvent volume ratio is between 0-3:10-7.
[0071] More specifically, the organic ammonium salt solution has a solvent volume of 50-200ul, a rotation speed of 1000-5000rpm, a rotation time of 10-80s, an annealing humidity of 10-50%, an annealing temperature of 60-180°C, and an annealing time of 10-50 min.
[0072] S14: preparing an electron transport layer 23 on the surface of the perovskite absorption layer 22, wherein the electron transport layer 23 is prepared by at least one of a spin coating method, a spray coating method or a vacuum deposition method, and the electron transport layer is zinc oxide (ZnO), tin dioxide (SnO2), titanium dioxide (TiO2), [6,6]-phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C 60 ) with a thickness of 10 to 25 nm;
[0073] Specifically, the electron transport layer 23 is formed by a spin coating method, wherein the electron transport layer dispersion is uniformly coated on the surface of the perovskite absorption layer 22, the spin coating speed is 500-4000 rpm, and the spin coating time is 10-80 s;
[0074] Specifically, the electron transport layer 23 is sprayed by preparing the electron transport layer dispersion and placing it in a spray box, starting the program, spraying at a height of 1 to 20 mm and a spraying speed of 0.1 to 3 cm / s, and removing the substrate after spraying is completed;
[0075] Specifically, the electron transport layer 23 adopts a vacuum deposition method to evaporate the electron transport layer material onto the surface of the perovskite absorption layer 22, and the evaporation vacuum degree is 5×10 -5 ~5×10 -4 Pa, the evaporation temperature is 100~400℃, and the evaporation rate is 0.05~1 Å / S;
[0076] S15: preparing an electrode layer 24 on the electron transport layer 23, wherein the electrode layer 24 is prepared by vacuum deposition or screen printing, and the electrode layer is at least one of gold (Au), silver (Ag), and copper (Cu), and has a thickness of 0 to 3000 nm;
[0077] Specifically, the electrode layer 24 is deposited by vacuum deposition. The substrate sample prepared in step S14 is placed on a mask plate for evaporation. The vacuum degree of evaporation is 5×10 -5 ~2×10 -4 Pa, the evaporation temperature is 500~2000℃, and the evaporation rate is 0.1~5 Å / S to obtain the electrode layer 24;
[0078] The electrode layer 24 may also be formed by screen printing, by printing metal grid lines with a thickness of 0-3000 um on the sample prepared in step S14.
[0079] The following specific embodiments are provided to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0080] Example 1
[0081] This embodiment provides a method for preparing a rectangular nanoimprint film perovskite solar cell, comprising the following steps:
[0082] S11: Providing a conductive substrate 20 and cleaning, respectively, using ethanol, methanol, acetone cleaning 15 min, drying 30min;
[0083] S12: Prepare a hole transport layer 21 on the surface of the conductive substrate 20 by spin coating, treat with UV-Ozone for 15 min before preparation, prepare a hole transport layer dispersion, weigh 0.05 mol NiO x The powder was dissolved in 1 ml ultrapure water and ultrasonically vibrated for 20 min. The hole transport layer dispersion was evenly coated on the surface of the sample. The spin coating speed was set to 2000 rpm, the spin coating time was 40 s, and the solution volume was 100 ul. After the spin coating, annealing was performed at 450 ° C and annealing time was 30 min to obtain the hole transport layer 21.
[0084] S13: Prepare a perovskite absorption layer 22, which is prepared by a two-step method and has a thickness of 500 nm; weigh 2 g of lead iodide material and place it in a crucible; place the battery substrate 10 on which the hole transport layer 21 is prepared in the above steps in a vacuum deposition substrate, and evacuate the substrate until the vacuum reaches 1×10 -4 Pa, the lead iodide crucible is heated to 380 ° C, the rate appears, the temperature is continued to rise to 410 ° C, the stable evaporation rate is 2Å / S, the baffle is opened for evaporation, and after evaporation to a thickness of 350nm, the baffle is closed and the heating of the lead iodide crucible is stopped, and a dense lead iodide film 11 is first prepared; then the nanoimprint film M1 prepared in advance is used, and the surface of the nanoimprint film M1 is composed of a plurality of square column structures arranged in an orderly array, and the lead iodide film 11 is further improved. 11 is pressed into an ordered shape and annealed on an annealing table at a temperature of 70°C for 30 seconds. The nanoimprint film is removed after annealing. An ultra-thin additive layer 13 is then prepared. 1g of propylenediamine bromide is placed in a crucible, and the imprinted lead iodide film substrate is placed in a vacuum deposition substrate. The vacuum is evacuated, and the additive crucible is heated to about 100°C at a steady rate of 0.1Å / S. The baffle is opened for evaporation. After 1nm is prepared, the baffle is closed and the heating of the additive crucible is stopped. Finally, 82 mg FAI, 10 mg MABr, and 9 mg MACl were dissolved in 1 ml ethanol to prepare an organic ammonium salt solution, and the prepared organic ammonium salt solution was evenly coated on the surface of the additive layer 13 to form an ammonium salt film 14. The amount of organic ammonium salt solution solvent was 130 ul, the rotation speed was 3000 rpm, and the rotation time was 40 s. After the rotation, annealing was performed in an environment with a humidity of 30%, the annealing temperature was 150°C, and the annealing time was 20 min to obtain a perovskite absorption layer 22.
[0085] S14: preparing an electron transport layer 23 on the surface of the perovskite absorption layer 22, specifically, 60 Evaporation to the surface of the perovskite absorption layer 22, the evaporation vacuum is 5×10 -4 Pa, evaporation rate at 0.1 Å / S;
[0086] S15: Prepare an electrode layer 24 on the electron transport layer 23 by vacuum deposition. The thickness of the electrode layer 24 is 200 nm. Cu is selected as the material of the electrode layer 24. The substrate sample prepared in step S14 is placed on a mask plate for evaporation. The evaporation vacuum is 2×10 -4 Pa, the evaporation temperature is about 2000°C, and the evaporation rate is 1 Å / S, to obtain the electrode layer 24;
[0087] Example 2
[0088] This embodiment provides a method for preparing a nanoimprinted film cone-shaped perovskite solar cell, except for step S13 of embodiment 1, the other steps are the same;
[0089] In this embodiment 2, S14: the surface of the nanoimprint film M1 is composed of a plurality of cones arranged in an orderly array.
[0090] Example 3
[0091] This embodiment provides a method for preparing a perovskite solar cell. Except for step S13 of embodiment 1, the other steps are the same.
[0092] In this embodiment 3, S13: prepare an ultra-thin additive layer 13, place 1g of additive material in a crucible, place the imprinted battery substrate in a vacuum deposition substrate, evacuate the vacuum, heat the additive crucible to about 100°C, stabilize the rate at 0.1Å / S, open the baffle for evaporation, and after preparing 1.5nm, close the baffle and stop heating the additive crucible.
[0093] Comparative Example 1
[0094] This comparative example provides a method for preparing a perovskite solar cell without a nanoimprint film, except for step S13 of Example 1, the other steps are the same;
[0095] In this comparative example 1, S13: 2 g of lead iodide material was weighed and placed in a crucible, and the battery substrate on which the hole transport layer 21 was prepared was placed in a vacuum deposition substrate, and vacuum was evacuated until the vacuum reached 1×10 -4 Pa, the lead iodide crucible is heated to 380℃, the rate appears, the temperature is continued to rise to 410℃, the evaporation rate is stabilized at 2Å / S, the baffle is opened for evaporation, and after evaporation to a thickness of 350nm, the baffle is closed and the heating of the lead iodide crucible is stopped, and a dense lead iodide film 11 is first prepared; 82mgFAI, 10mgMABr, and 9mgMACl are dissolved in 1mlethanol to prepare an organic ammonium salt solution, and the prepared organic ammonium salt solution is evenly applied to the surface of the above-mentioned film layer, the solvent volume of the organic ammonium salt solution is 130ul, the rotation speed is 3000rpm, and the rotation time is 40s. After the rotation, annealing is carried out in an environment with a humidity of 30%, the annealing temperature is 150℃, and the annealing time is 20 min to obtain a perovskite absorption layer 22.
[0096] A solar simulator was used to perform a standard solar intensity calibration (AM1), and the area of Comparative Example 1 and Example 2 was 0.09 cm 2 The area of Example 3 is 0.8 cm 2The devices obtained in the above embodiments and comparative examples are subjected to IV tests, including photoelectric conversion efficiency (PCE), fill factor (FF), open circuit voltage (Voc) and short circuit current (Jsc). Specifically, the energy conversion efficiency of the perovskite cells of each embodiment and comparative example is measured. Under atmospheric environment, the sunlight simulation light source uses the AM1.5G standard light source, and a four-channel digital source meter (Keithley 2440) is used to measure the volt-ampere characteristic curve of the battery under the irradiation of the light source to obtain the open circuit voltage Voc, short circuit current density Jsc, and fill factor FF of the battery, thereby calculating the energy conversion efficiency Eff of the battery. Eff=Pout / Popt= Voc×Jsc×(Vmpp×Jmpp) / (Voc×Jsc)= Voc×Jsc×FF, where Pout, Popt, Vmpp, and Jmpp are the battery operating output power, incident light power, battery maximum power point voltage, and maximum power point current, respectively.
[0097] The starting voltage of Example 1, Example 2, Example 3 and Comparative Example 1 is set to 1.2V, the cut-off voltage is 0V, the range is 100 mA, and the result is rounded to two decimal places. The test results are shown in Table 1 below:
[0098] Table 1 Devices <![CDATA[Jsc(mA / cm 2 )]]> Voc(V) FF(%) EFF(%) Example 1 1.15 20.20 79.21 18.41 Example 2 1.14 20.08 78.89 18.05 Example 3 1.13 20.32 78.55 18.03 Comparative Example 1 1.06 20.83 74.86 16.52
[0099] Based on the comparative analysis of the above table data, the method for preparing a perovskite solar cell provided in this application has at least the following beneficial effects:
[0100] The present invention utilizes a nanoimprint film to improve a conventional lead iodide film to form an ordered lead iodide film, which is more conducive to complete reaction, can effectively reduce the residual lead iodide content, and reduce defects. The preparation method of the present invention first improves the lead iodide film and then deposits an ultra-thin additive layer, so that the additive can effectively participate in the reaction process, improve the film quality of the perovskite absorption layer, and improve the device performance, and provides a new idea for the additive doping approach in the two-step perovskite preparation method.
[0101] The preparation method of the present invention is low-cost, simple to operate, and improves the photoelectric performance of the device, and is expected to be applied in the preparation of large-area perovskite solar cells.
[0102] The above embodiments are only preferred implementation modes of the present invention. It should be pointed out that for ordinary technicians in this technical field, various changes, modifications, substitutions and deformations can be made to these embodiments without departing from the principles of the present invention. These technical solutions that are equivalent to the claims of the present invention all fall within the protection scope of the present invention, and the protection scope of the present invention is limited by the attached claims and their equivalents.
Claims
1. A method for preparing a perovskite film, characterized in that: The method comprises the following steps: providing a battery substrate, preparing a lead iodide film on the battery substrate; using a nanoimprint film to further improve the lead iodide film to form a patterned lead iodide film, and pressing the lead iodide film into an ordered shape; depositing an additive layer on the surface of the patterned lead iodide film by a vacuum deposition method; coating the surface of the additive layer with a prepared organic ammonium salt solution to form an ammonium salt film, and obtaining a perovskite absorption layer after spin coating and annealing.
2. The method for preparing a perovskite thin film according to claim 1, characterized in that: The surface of the nanoimprint film is provided with a plurality of array-distributed strip-shaped protrusion structures, wherein the strip-shaped protrusion structures are selected from one of arch, cone, and square; or, the surface of the nanoimprint film is provided with a plurality of array-distributed point-shaped protrusion structures, wherein the point-shaped protrusion structures are selected from one of cone, cylinder, and cube.
3. The method for preparing a perovskite thin film according to claim 2, characterized in that: The cross-sectional width of the strip-shaped protruding structure or the width of the dot-shaped protruding structure is defined as d1, and the spacing between the strip-shaped protruding structures or the spacing between the dot-shaped protruding structures is defined as d2. The d1 is 0.5-2 μm, and the d2 is 0.5-3 μm.
4. The method for preparing a perovskite thin film according to claim 3, characterized in that: The d1 is 1 μm, and the d2 is 2 μm.
5. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The nanoimprint film material is flexible polysiloxane.
6. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The battery substrate comprises a conductive substrate and a hole transport layer thereon; or, the battery substrate is a back electrode, a silicon bottom battery, a tunneling layer and a hole transport layer stacked in sequence, and the silicon bottom battery is a non-textured structure.
7. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The lead iodide film is deposited on the battery substrate by vacuum evaporation. The vacuum range of the lead iodide film during evaporation is 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~8Å / S, the heating crucible temperature is 380℃~500℃, and the evaporation time is 30min~4h.
8. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The vacuum degree of the additive layer during vacuum deposition is in the range of 5×10 -4 Pa~1×10 -2 Pa, the evaporation rate range is 0.1Å / S~1Å / S, the heating crucible temperature is 100℃~200℃, the evaporation time is 5min~20min, and the thickness is 0.5~5nm.
9. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The additive layer is an organic amine halide, including one of propylene diamine bromide (PDADBr), propylene diamine iodide (PDADI), butyl amine iodide (BAI), and dodecanediaminium bromide (DDDADBr); Alternatively, the additive layer is a bromide, a chloride or a rubidium compound, including one of cesium bromide (CsBr), cesium fluoride (CsF), cesium chloride (CsCl), rubidium chloride (RbCl) and rubidium bromide (RbBr).
10. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The organic ammonium salt solution is prepared by dissolving formamidine iodide (FAI), formamidine bromide (FABr) and methylammonium chloride (MACl) in an organic solvent in a certain proportion, and the concentration of the solution is controlled between 0.5 and 2 M; the organic solvent includes at least one of ethanol, isopropanol, methanol, dimethylformamide (DMF), G-butyrolactone (GBL), dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMA).
11. The method for preparing a perovskite thin film according to any one of claims 1 to 4, characterized in that: The solvent volume of the organic ammonium salt solution is 50-200ul, the rotation speed of the spin coating is 1000-5000rpm, the rotation time is 10-80s, the annealing humidity is 10-50%, the annealing temperature is 60-180°C, and the annealing time is 10-50 min.
12. A perovskite solar cell, characterized in that: The structure comprises, from bottom to top, a conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer, and an electrode layer. The perovskite absorption layer is obtained by the perovskite film preparation method according to any one of claims 1 to 11.
13. The method for preparing a perovskite solar cell according to claim 12, characterized in that: The method comprises the following steps: providing a conductive substrate, preparing a hole transport layer on the surface of the conductive substrate, preparing a perovskite absorption layer on the surface of the hole transport layer, preparing an electron transport layer on the surface of the perovskite absorption layer, and preparing an electrode layer on the surface of the electron transport layer.
Citation Information
Patent Citations
Preparation method of surface-patterned organic-inorganic hybrid perovskite thin film
CN114122266A
Method for preparing high-performance perovskite thin film from ordered porous lead iodide and application of high-performance perovskite thin film
CN115605063A
Method for preparing perovskite thin film through porous dissolution and laminated solar cell
CN117715485A
Inversion wide-band-gap perovskite solar cell and preparation method thereof
CN118251022A
Perovskite layer preparation method, laminated solar cell and preparation method
CN118890941A
Cited By
Perovskite solar cell and preparation method thereof
CN120035355A